Exploring Metatextuality in the English Writing of Multilingual Students at Sekolah Indonesia Kuala Lumpur - Videyarani, Azzahra Fitri; Madjid, Hilda Izzati; Hasnawati, Lina (ICONELT, 2024)
Intertextuality connects texts across cultures, enabling multilingual students to creatively draw from diverse sources and enrich broader literacy discourses. This research used discourse analysis model to examine metatextuality in multilingual students' English writing grade 11 for the 2023/2024 academic year at Sekolah Indonesia Kuala Lumpur, analyzing how social practices influence language use and linking metatextual elements to current phenomena. This study revealed 74 metatextual elements in 197 sentences, categorized as external and internal. These findings underscore students' advanced language skills and cultural awareness, highlighting the importance of intertextual analysis in understanding the complexity of multilingual students' writing.